2009
DOI: 10.1152/ajpregu.91013.2008
|View full text |Cite
|
Sign up to set email alerts
|

Social stress-induced bladder dysfunction: potential role of corticotropin-releasing factor

Abstract: Wood SK, Baez MA, Bhatnagar S, Valentino RJ. Social stress-induced bladder dysfunction: potential role of corticotropin-releasing factor. Am J Physiol Regul Integr Comp Physiol 296: R1671-R1678, 2009. First published May 11, 2009 doi:10.1152/ajpregu.91013.2008.-Psychological stress can impact on visceral function with pathological consequences, although the mechanisms underlying this are poorly understood. Here we demonstrate that social stress produces marked changes in bladder structure and function. Male r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
134
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(143 citation statements)
references
References 52 publications
8
134
1
Order By: Relevance
“…Thus, discrete chemical activation of Barrington's nucleus neurons elicited bladder contractions that were increased by intrathecal administration of a CRF antagonist, and conversely, decreased by intrathecal CRF. An inhibitory role for CRF in Barrington's nucleus regulation of the bladder is consistent with reports that social stress in rodents leads to urinary retention, abnormal urodynamics, and bladder hypertrophy (4,6,12,13,45), and this is associated with increased expression of CRF in Barrington's nucleus neurons (45). These findings suggest that pharmacological manipulation of CRF may improve bladder dysfunctions associated with stress or other conditions.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Thus, discrete chemical activation of Barrington's nucleus neurons elicited bladder contractions that were increased by intrathecal administration of a CRF antagonist, and conversely, decreased by intrathecal CRF. An inhibitory role for CRF in Barrington's nucleus regulation of the bladder is consistent with reports that social stress in rodents leads to urinary retention, abnormal urodynamics, and bladder hypertrophy (4,6,12,13,45), and this is associated with increased expression of CRF in Barrington's nucleus neurons (45). These findings suggest that pharmacological manipulation of CRF may improve bladder dysfunctions associated with stress or other conditions.…”
supporting
confidence: 88%
“…Brain sections collected on slides were postfixed by incubation in 10% formalin and processed to quantify CRF mRNA, as previously described (42). Sections containing Barrington's nucleus were hybridized with an antisense riboprobe to CRF mRNA (Dr. Audrey F. Seasholtz, University of Michigan) and coated with Kodak NTB2 liquid autoradiographic emulsion (7-day exposure at 4°C) identical to that previously published (45). The tissue was lightly stained with cresyl violet, and bright-field images were cap-tured and magnified using Open Lab software to identify cresyl violet-stained cells containing silver grains greater than 2-4 times background.…”
mentioning
confidence: 99%
“…For example, rats exposed to various types of stress (water avoidance, intruder stress) exhibit symptoms of bladder dysfunction including increased micturition frequency as well as anxiety-like behavior (257,299). Furthermore, an exaggerated acoustic startle response has been demonstrated in both cats diagnosed with FIC as well as in BPS/IC patients (279,296).…”
Section: A Bladder Pain Syndromementioning
confidence: 99%
“…Studies on molecular mechanisms through which CRH is stimulated in these areas lag behind compared to that of PVH. It has been shown that psychosocial stress increases CRH mRNA levels in the CeA (Hsu et al 1998, Kalin et al 1994 and laterodorsal (oval) subnucleus of BNST (Makino et al 1999) and in the Barrington's nucleus (Wood et al 2009). Although CRH mRNA is elevated in both of…”
Section: Regulation and Function Of Central (Extrahypophyseotropic) Crhmentioning
confidence: 99%
“…Expression of CRH mRNA in these neurons is upregulated in response to stress (Wood et al 2009), but not to ADX (Imaki et al 1991). Increase of CRH in Barrington's nucleus by social stress has been linked to stress-induced bladder disfunction (Wood et al 2009, Wood et al 2013.…”
Section: Regulation and Function Of Central (Extrahypophyseotropic) Crhmentioning
confidence: 99%